Respuesta :
Answer:
[tex]s^3+3s^2t+3st^2+t^3[/tex]
Step-by-step explanation:
[tex](s+t)^3\\\\\mathrm{Apply\:Perfect\:Cube\:Formula}:\\\quad \left(a+b\right)^3=a^3+3a^2b+3ab^2+b^3\\\\a=s,\:\:b=t\\=s^3+3s^2t+3st^2+t^3[/tex]
Step-by-step explanation:
Hey there!
Here, given;
[tex]( {s + t)}^{3} [/tex]
Use formula:
[tex]( {a + b)}^{3} = {a}^{3} + 3 {a}^{2}b + 3a {b}^{2} + {b}^{3} [/tex]
Keep this formula in the question.
[tex]( {s + t)}^{ 3} = {s}^{3} + 3 {s}^{2} t + 3s {t}^{2} + {t}^{3} [/tex]
Hope it helps...